Anodic stripping voltammetric determination of aurothiomalate in urine using a screen-printed carbon electrode - Bergamini, Marcio F.; Zanoni, Maria Valnice Boldrin [UNESP] (Wiley-Blackwell, 2006)
This work describes an electroanalytical method for determining gold(I) thiomalate, aurothiomalate, widely used for treatment of reumatoid arthiritis, using a screen-printed carbon electrode (SPCE). Aurothiomalate (AuTM) was determined indirectly at the same electrode by accumulating it first at -1.5 V vs. printed carbon. At this potential in the adsorbed state, the AuTM is reduced to Au(0), which is then oxidized at two steps at -0.22 V and +0.54 V on SPCE. Using optimized conditions of 60 s deposition time, -1.5 V (vs. printed carbon) accumulation potential, 100 mV s(-1) scan rate, linear calibration graphs can be obtained by monitoring the peak at +0.54 V for AuTM in HCl 0.1 mol L-1 from 1.43 x 10(-6) to 1.55 x 10(-4) mol L-1. A limit of detection obtained was 6.50 x 10(-7) mol L-1, and the relative standard deviation from five measurements of 3.0 x 10(-5) mol L-1 AuTM is 4.5%. The method was successfully applied for AuTM determination in human urine sample.
Keywords: sodium aurothiomalate; gold(I) thiolate determination; screen-printed electrode; gold-base drugs